Analisis Peran Sektor Basis dan Non Basis dalam Penyerapan Tenaga Kerja di Kabupaten Gresik - Hadina Rizky Amalia; Herry Yulistiyono (Jurnal Ilmiah Aset, 2020)
This research aims to identify base and non-base sectors and analyze the absorption of labor in the base and non-base sectors in Gresik Regency as informationand consideration in economic development planning. This research is a descriptive quantitative study using secondary data of PDRB variables and labor and its components in Gresik Regency. The analytical methods used in this study are LQ analysis, shiftshare analysis, MRP analysis and labor absorption analysis. The results of the LQ analysis show the processing industry sector, the mining and quarrying sectors and the electricity and gas procurement sector are the base sectors. The results of the shiftshare analysis show sectors where the average power growth is higher than overall economic growth are the agricultural sector, the provision of drinking accommodation, construction, trade, transportation and warehousing, information and communication, financial services, corporate services, education services and the healthcare sector. While the sectors whose average local competitiveness growth is higher than the competitiveness of the same sector in East Java Province are agriculture, electricity procurement, water procurement, construction, trade, information and communication, food and drink accommodation provision sector, corporate services sector, government administration, education services, health and other service sectors. The results of the MRP analysis also show that the electricity and gas procurement sector is the leading sector in terms of growth. From the analysis of labor elasticity, it is known that the average sector with the highest labor elasticity value in 2011-2015 is the base sector, namely the mining sector and the electricity and gas procurement sector and in 2016-2017 is the non-base sector, namely the transportation sector and financial institutions.